2014
DOI: 10.1371/journal.pone.0097636
|View full text |Cite
|
Sign up to set email alerts
|

Allelic Variations at Four Major Maturity E Genes and Transcriptional Abundance of the E1 Gene Are Associated with Flowering Time and Maturity of Soybean Cultivars

Abstract: The time to flowering and maturity are ecologically and agronomically important traits for soybean landrace and cultivar adaptation. As a typical short-day crop, long day conditions in the high-latitude regions require soybean cultivars with photoperiod insensitivity that can mature before frost. Although the molecular basis of four major E loci (E1 to E4) have been deciphered, it is not quite clear whether, or to what degree, genetic variation and the expression level of the four E genes are associated with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
64
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(71 citation statements)
references
References 35 publications
2
64
1
1
Order By: Relevance
“…The averaged data for triplicated trials were analyzed statistically for assessments of plant growth and yield components in three studied locations. The accessions were genotyped for E1 , E2 , E3 , and E4 alleles according to protocols published elsewhere [5], [19], [20], [14], respectively. DNA extraction and agarose gel electrophoresis were performed according to Abugalieva et al [17].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The averaged data for triplicated trials were analyzed statistically for assessments of plant growth and yield components in three studied locations. The accessions were genotyped for E1 , E2 , E3 , and E4 alleles according to protocols published elsewhere [5], [19], [20], [14], respectively. DNA extraction and agarose gel electrophoresis were performed according to Abugalieva et al [17].…”
Section: Methodsmentioning
confidence: 99%
“…The productivity of soybean is largely dependent on flowering and maturity times in diverse ecological environments [2], [5], [6], [7]. Therefore, in Northern America 13 maturity groups (MG) were classified for breeding purposes [8].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Of these, the E1-E4 and E7 loci are responsible for photoperiodic control of flowering time (Watanabe et al, 2012;Zhai et al, 2014). Mapping of the E2/ FT2 locus showed that the responsible gene is GmGIa, a soybean homolog of AtGI (Watanabe et al, 2011).…”
Section: Orthologs Ofmentioning
confidence: 99%